Powerful ideas?: Decolonisation and the future of global health - Hellowell, Mark; Schwerdtle, Patricia (BMJ global health, 2022)
Summary box - Calls to ‘decolonise’ global health have intensified in recent years, as reflected in the rapid growth of the academic literature on this concept.1-6 This body of work (henceforth: ’the literature‘) draws on the conceptual frameworks and interpretive lenses of Critical Race Theory and related analyses of structural racism in Western countries 7 8 alongside postcolonial theory and related analyses of colonialism’s cultural, psychological and material impacts and legacies, especially in the ‘Global South’.9 10 The literature calls attention to asymmetries in the distribution of epistemic authority and decision-making power in global health and argues that these have their origins in colonialism and continue to advantage and empower some persons over others, depending on their race, ethnicity and place of origin - with the disadvantaged group comprising Indigenous communities and ethnic minorities in the 'Global North', and black people and people of colour in the 'Global South'.11 12 - - There is a range of different arguments about the best methods for addressing these asymmetries. Authors affiliated to the Global Health Decolonisation Movement in Africa emphasise …